A Legal Appraisal of the Application of the Death Penalty in Cameroon - NTOKO NTONGA Rene; Edward LYONGA EWULE Esq; ENOW Godwill BAIYE; MIKANO Emmanuel KIYE (Studies in Law and Justice, 2024)
This paper provides a comprehensive legal appraisal of the death penalty’s application in Cameroon, evaluating its constitutional, legal, and human rights dimensions. Despite the global trend towards abolition, Cameroon continues to implement capital punishment, sparking intense debate regarding its alignment with international human rights standards and constitutional guarantees. The study examines the statutory framework governing the death penalty in Cameroon, including relevant provisions of the Cameroonian Penal Code and the Constitution. It assesses the recent legal reforms and international treaties on the death penalty’s application. Through a critical analysis of judicial practices, and case law, the paper highlights inconsistencies and challenges in the implementation process. The appraisal further explores the socio-political and ethical implications of capital punishment in Cameroon, considering public opinion and the role of civil society. The study adopts a qualitative research methodology which makes use of empirical methods such as observation. It also makes use of the doctrinal method which entails content analysis of primary and secondary data. Ultimately, the study advocates for a reassessment of the death penalty’s role in the justice system, emphasizing the need for reforms to align with evolving human rights norms and ensure fair and equitable application of justice.